Structural analysis - Hibbeler, R. C (Pearson, 2017)
Includes index.; Types of structures and loads -- Analysis of statically determinate structures -- Analysis of statically determinate trusses -- Internal loadings developed in structural members -- Cables and arches -- Influence lines for statically determinate structures -- Approximate analysis of statically indeterminate structures -- -- Deflections -- Deflections using energy methods -- Analysis of statically indeterminate structures by the force method -- Displacement method of analysis : slope-deflection equations -- Displacement method of analysis : moment distribution -- Beams and frames having nonprismatic members -- Truss analysis using the stiffness method -- Beam analysis using the stiffness method -- Plane frame analysis using the stiffness method -- Appendices